Development of Web-Based Komsa Media to Facilitate Logical Thinking and Reading Habits At Elementary School Level - Ardini, Kasimira Prima; Widayat, Edy; Huda, Nuril (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Science lessons often involve conceptual material that requires visualization to facilitate studentsâ€™ understanding. In the fifth grade science learning process, it was found that students had difficulty understanding the subject, lacked enthusiasm for reading, Â and the learning media used were monotonous and uninteresting. Consequently, this affected studentsâ€™ logical thinking abilities. The purpose of this research is to determine the feasibility and effectiveness of the Science Comic (KOMSA) media as a tool to facilitate the logical thinking abilities and reading habits of fifth-grade students in elementary school, specifically on the topic of the water cycle. This study is a developmental research using the 4D approach (define, design, develop, disseminate) with a one-group pretest-posttest design technique conducted at Pangudiluhur Ambarawa Elementary School. The discussion results obtained an average percentage of 87%. The trial results indicated that the learning media falls into the category of high effectiveness with a percentage of 77.18%. Therefore, the Science Comic (KOMSA) as a learning media is deemed suitable and effective for facilitating logical thinking abilities and reading habits. Â